(untitled) (Jurnal Bina Praja, 2023)
Implementing government affairs with broad autonomy, especially elective government affairs can promote and develop regional potential. However, in its regulation and implementation, some problems hamper creativity and the development of regional potential. This study aims to evaluate the development and practice of elective government affairs in Indonesia, find a way to strengthen elective government affairs, and realize the widest possible autonomy in the Unitary State of the Republic of Indonesia system. The research used normative law through a statutory, conceptual, and historical approach. The results showed that first, the development of regulations governing government affairs in Indonesia is only explicitly regulated in two laws, namely Law 32/2004 and Law 23/2014. On the other hand, this study found anomalies in the regulation of elective government affairs in Law 23/2014, namely that not all selected government affairs are delegated to provinces and districts/cities even though elective affairs have very potential in developing the potential and distinctiveness of the region. Not only that, in practice, selected government affairs are sometimes hampered by the application of NSPK from the central government. Second, the strengthening of selected government affairs to implement the widest possible autonomy can be done by strengthening selected government affairs based on the NKRI system and redesigning NSPK in the implementation of selected government affairs in the regions.